Single agent lenalidomide activity in multiple myeloma relapse evidenced uniquely by CT/PET - Alessandro Gozzetti; Vania Rossi; Alfonso Cerase; Giulia Papini; Marzia Defina; Monica Bocchia (Mediterranean Journal of Hematology and Infectious Diseases)
A71 year old female with multiple myeloma presented with back pain seven year after autologous stem cell transplant. Skeletal bone survey and magnetic resonance imaging did not show a relapse that was evidenced by CT/PET. Lenalidomide as single agent induced a complete disappearance of the lesions 6 months later at CT/PET